The Analgesic Efficacy of Intravenous Dexamethasone for Postcesarean Pain: A Systematic Review With Meta-analysis and Trial Sequential Analysis. Issue 1 (22nd March 2023) - Singh, N.P.; Makkar, J.K.; Yadav, N.; Goudra, B.G.; Singh, P.M.
Abstract : ( Eur J Anaesthesiol . 2022;39:498–510) Pain management during and following cesarean delivery (CD) has been a topic of interest due to its impact on maternal outcomes, yet the efficacy of intravenous dexamethasone for post-CD analgesia requires more analysis. This systematic review and meta-analysis investigated the association of dexamethasone administration and pain following CD compared with a control group.